The Effect of Domestic Debt on Economic Growth in Malaysia - Muhamad Sufiyan, Md Rahman (2011)
This study analyzes the effects of domestic debt on economy growth in Malaysia for the period of 1996 to 2009 using quarterly data, and provides recommendations on how to improve domestic debt management in Malaysia. The purpose of this paper is to examine the relationship between Treasury Bills, Government Securities and GDP. This study employs a function which includes treasury bills, investment issues, financial sector, social security institutions, insurance companies, public sector, and foreign holder as the potential determinants of domestic debt. The empirical analysis is based on time series data for 14 years. The model tested for a long run relationship using the Johansen and Juselius cointegration approach shows that treasury bills, investment issues, public sector, social security institutions, insurance companies, and financial sector are the determinants of domestic debt in the long run. On the other hand, results based on the Error Correction Model (ECM) show that treasury bills, investment issues, social security institutions, insurance companies, financial sector, and foreign holder are the significant determinants of domestic debt in a short run. Furthermore, variable ECM which indicates the speed of adjustment shows that 1.4 percent of the adjustment is completed in a year. The results obtained in the study suggest that policymakers should keep an eye on all of the significant variables since they affect economic growth.